2023
DOI: 10.1002/nop2.1650
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patterns of kinesiophobia trajectories among COPD patients: A longitudinal study

Abstract: Aim To determine differences in kinesiophobia levels among COPD patients at different time points 6 months after discharge;To identify potential subgroups of COPD patients who perceived different levels of kinesiophobia over time;and to evaluate differences in identified subgroups based on demographic and disease‐related characteristics Design An observational longitudinal study. Methods O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…Different from the research carried out by Liang [ 15 ], kinesiophobia among patients undergoing TKA showed four trajectories. The low stable group and moderate stable group in our study were very similar to the low kinesiophobia group and medium kinesiophobia group in Liang’s study.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Different from the research carried out by Liang [ 15 ], kinesiophobia among patients undergoing TKA showed four trajectories. The low stable group and moderate stable group in our study were very similar to the low kinesiophobia group and medium kinesiophobia group in Liang’s study.…”
Section: Discussioncontrasting
confidence: 71%
“…Latent class growth analysis (LCGA) can capture information about interindividual differences in the change of kinesiophobia over time and identify participants with similar kinesiophobia trajectories [ 14 ]. Liang has identified three distinct trajectories of kinesiophobia in a sample of participants with chronic obstructive pulmonary disease [ 15 ]. The three groups were named low kinesiophobia, medium kinesiophobia, and high kinesiophobia group, respectively.…”
Section: Introductionmentioning
confidence: 99%